2020
DOI: 10.1038/s41392-020-00256-x
|View full text |Cite
|
Sign up to set email alerts
|

The model of cytokine release syndrome in CAR T-cell treatment for B-cell non-Hodgkin lymphoma

Abstract: Chimeric antigen receptor T (CAR T) cell therapy has demonstrated efficacy in the treatment of haematologic malignancies. However, the accompanying adverse events, the most common of which is cytokine release syndrome (CRS), substantially limit its wide application. Due to its unique physiological characteristics, CRS in CAR T-cell treatment for B-cell non-Hodgkin lymphoma (B-NHL) may exhibit some special features. Although existing guidelines had greatly promoted the recognition and management of CRS, many re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 106 publications
4
102
0
Order By: Relevance
“…After co-culturing with αvβ6-positive cells, A20-2G CAR T cells produced greater levels of IFN-γ than A20-4G CAR T cells (4.5±1.9% vs. 1.1±0.7%; p =0.0156) ( Figures 6A,B ). This may be an advantage of A20-4G CAR T cells since clinical studies of the 4G CAR T cells targeting CD19 found that low levels of IFN-γ might be beneficial to limit CAR T cell-mediated cytokine release syndrome (CRS) ( 10 , 15 ), which was often observed in patients who received CAR T cell therapy ( 48 , 49 ). Furthermore, A20-4G CAR T cells showed a higher proliferation rate than A20-2G CAR T cells (74.6±5.9% vs. 56.5±5.5%, p =0.0175) ( Figures 6C,D ).…”
Section: Discussionmentioning
confidence: 99%
“…After co-culturing with αvβ6-positive cells, A20-2G CAR T cells produced greater levels of IFN-γ than A20-4G CAR T cells (4.5±1.9% vs. 1.1±0.7%; p =0.0156) ( Figures 6A,B ). This may be an advantage of A20-4G CAR T cells since clinical studies of the 4G CAR T cells targeting CD19 found that low levels of IFN-γ might be beneficial to limit CAR T cell-mediated cytokine release syndrome (CRS) ( 10 , 15 ), which was often observed in patients who received CAR T cell therapy ( 48 , 49 ). Furthermore, A20-4G CAR T cells showed a higher proliferation rate than A20-2G CAR T cells (74.6±5.9% vs. 56.5±5.5%, p =0.0175) ( Figures 6C,D ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our T cell studies, VISTA agonists likely would exert minimal inhibitory impact on activated CAR T cells directly. However, we understand that CAR T cells activate macrophages or neutrophils to cause organ damage and other adverse events ( 52 ). As a result, heightened cytokine production from myeloid cells likely contribute to CRS and agonistic targeting of VISTA may ameliorate the innate components of the CAR T induced CRS.…”
Section: Vista Induce Myeloid Reprogramming: Evidence For Profound Rementioning
confidence: 99%
“…An important aspect to consider in CAR-T cells is the potential side effects due to overstimulation and/or inadequate stimulation. Severe CRS (grades 3 or 4) is an important hallmark in CD19+ that can compromise efficacy and lead to life-threatening conditions 28,29 . Upon tumour cell encounter, CAR-T cells release different pro-inflammatory cytokines such as TNFα, IFN□, IL-1 and GM-CSF that leads to macrophage recruitment and activation causing a dangerous cytokine storm involving IL-6 and GM-CSF 30, 31 .…”
Section: Discussionmentioning
confidence: 99%